Energy-efficient Joint Power Allocation and Channel Selection for D2D Communications - Ma, Guifang; Zhou, Zhenyu; Bai, Jinfang (EAI Endorsed Transactions on Energy Web, 2015)
Device-to-device (D2D) communications have gained great attentions due to the potential and numerous benefits for cellular networks. However,it also brings tremendous resource allocation challenges for the sake of the constraint of battery life. Up to now, there are limited works attempt to prolong the battery life by improving the energy efficiency (EE). In this paper, we study how to perform resource allocation to increase EE in a interference limited environment under a noncooperative game model. Each D2D pair can reuse all or part of the channel resources allocated to cellular users. An energy-efficient joint power allocation and channel selection is proposed by employing the nonlinear fractional programming. We obtain the optimal power allocation and channel selection through an iterative algorithm called Dinkelbach method. Finally, the algorithm proposed in this paper is verified by simulation.